Combination of Chitosan and Essential Oils for Tomatoes Protection Against the Insect Pest Spodoptera littoralis (Lepidoptera: Noctuidae) - Thomas Drozdz; Philippe Couzi; Manuel Massot; Barbara Conti; Roberta Ascrizzi; David Siaussat (Insects)
Tomatoes are one of the most popular vegetables. The high level of production in the world is often offset by numerous losses that occur during production in the field or in the post-production stages. Preservation in its fresh form is a challenge, particularly due to pest attacks on stored food. A promising natural and inexpensive solution to protect against pests is the use of chitosan (CH), which can be associated with essential oils (EOs) with repellent effects. In previous studies, some protective effects have been demonstrated using chitosan films coated with EOs. In this study, we tested CH-EOs associations on tomato fruits to evaluate their efficacy against attacks by the pest Spodoptera littoralis (Boisduval, 1833), taking into account parameters such as age and body mass of the larvae and the effect over time (10 days) of the treatments. Our study highlights the potential of the combination of CH and cinnamon EO as an environmentally friendly solution to protect tomatoes from S. littoralis attack. Here we found a repellent effect of cinnamon EO combined with CH on S. littoralis larvae, with no effect on larval attractiveness or repellence for CH alone and the four other EOs tested. The main compound in cinnamon EO, (E)-cinnamaldehyde, had no overall repellent effect on larvae, but had specific effects when larval age, body mass, and post-treatment time were taken into account.